An EXAFS approach to the study of polyoxometalate–proteiniInteractions: the case of decavanadate–actin - Marques, M. P. M. (2017)
Decavanadate−actin interactions were studied by EXAFS and XANES, allowing us to simultaneously probe, for the first time, all vanadium species in the system. V10 interacts with G-actin (at its ATP binding site), a V−SCys coordination having been verified along with oxidovanadium formation. V10’s interplay with F-actin was found to be weak and occur via a different mechanism. These results are relevant for understanding V10’s biological roles, at a molecular level, aiming at potential pharmacological applications.